Caristi Type Selections of Multivalued Mappings. (11th January 2015) - Vetro, Calogero; Vetro, Francesca
Abstract : Multivalued mappings and related selection theorems are fundamental tools in many branches of mathematics and applied sciences. In this paper we continue this theory and prove the existence of Caristi type selections for generalized multivalued contractions on complete metric spaces, by using some classes of functions. Also we prove fixed point and quasi-fixed point theorems.